Inovasi Kepala Desa Menginisiasi Desa Digital untuk Kesejahteraan Rakyat: Studi Kasus di Desa Hadakewa, Kabupaten Lembata, NTT - Pariangu, Umbu TW (Prodi Sosiologi FISIP Universitas Teuku Umar, 2023)
Villages, as the smallest communities, have not escaped the flood of communication technology or what is known as the global village. Demands for change that challenge physical mobility, ideas, methods and ways of working that are faster, more innovative, more effective and efficient force villages to speed up their adaptation. This article aims to describe the innovative steps taken by the Head of Hadakewa Village. This qualitative descriptive research is based on case studies where quantitative and qualitative data are collected from various sources of information and their derivatives, either through direct observation, research or enrichment studies through information from books, journals, electronic media and other relevant reading sources. The results of this research show that the village head is able to innovate by digitalizing the management of the village's superior potential (tourism and fisheries), involving the participation of the community, regional and central government and the private sector. The synergy of this innovation ecosystem is important to be adopted by other villages in Indonesia as an innovative strategy to create prosperous villages.